1994
DOI: 10.1007/bf01473224
|View full text |Cite
|
Sign up to set email alerts
|

On P-mode oscillations in stars from 1M ? to 2M ?

Abstract: A b s t r a c t . The structure of stars more massive than about 1.2M® is characterized by a convective core. We have studied the evolution with age and mass of acoustic frequencies of high radial order n and low degree l for models of stars of 1, 1.5 and 2 M®. Using a polynomial approximation for the frequency, the p-mode spectrum can be characterized by derived global asteroseismic coefficients, i.e. the mean separation ~0 ~ vn,~ -vn-l,~ and the small frequency separation A~0,~ ~ vn,~=0 -vn-l,~=2. The diagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…As for the A&A 550, A126 (2013) Sun, one may question using the asymptotic expansion, since the quality of the data usually allows one to go beyond this approximate relation. Moreover, modeling has shown that acoustic glitches due to discontinuities or important gradients in the stellar structure may hamper the use of the asymptotic expansion (e.g., Audard & Provost 1994).…”
Section: Introductionmentioning
confidence: 99%
“…As for the A&A 550, A126 (2013) Sun, one may question using the asymptotic expansion, since the quality of the data usually allows one to go beyond this approximate relation. Moreover, modeling has shown that acoustic glitches due to discontinuities or important gradients in the stellar structure may hamper the use of the asymptotic expansion (e.g., Audard & Provost 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, the expressions of the scaled small separation and of the σ l−1l+1 (n) are obtained from an approximative expression of frequency ν n,l , which is inaccurate (Roxburgh & Vorontsov 1994a;Audard & Provost 1994). Although Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…1, we compare the separations d ll+2 (n)/(2l + 3) and σ l−1l+1 (n) obtained from the asymptotic formulas (10) and (15) with the separations obtained from the numerically computed frequencies. The discrepancy between the asymptotic and the numerical values is large, as has been shown by Roxburgh & Vorontsov (1994a) and Audard & Provost (1994). Equations (10) and (15) obtained from the asymptotic formula (6) are inaccurate.…”
Section: Asymptotic Formula and Frequency Separationsmentioning
confidence: 95%
See 2 more Smart Citations